Реакция упругого пространства на бегущую вдоль двухслойной оболочки нагрузку - Гирнис, С. Р.; Украинец, В. Н. (НТУ "ХПИ", 2008)
На модельній задачі про дію рухомого навантаження в підкріпленому обробленням круговому тунелі, розташованого в пружнім просторі, досліджується його динамічна поведінка. Для опису руху кріплення тунелю використовуються класичні рівняння теорії тонких оболонок і динамічні рівняння теорії пружності.

On the base of model problem about action of mobile load in the supported by the double-layer winding circular cross section tunnel, placed in elastic space is researched its dynamic action. For describing motion of the inner ply of the support are used classic formulas of the fine cases theory, and for description of the motion its facing and ambient - dynamic formulas of the elasticity theory.
Keywords: цилиндрическая оболочка; механико-математическая модель; теория тонких оболочек; динамические уравнения; потенциалы Ламе; функции Бесселя; коэффициенты рядов Фурье-Бесселя